Edukasi Literasi Keuangan Syariah Bagi Petani di Desa Talang Jarang Kecamatan Air Napal Kabupaten Bengkulu Utara - Necko Rahmat Novianto; Idwal B; Nonie Afrianty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to educate the community in Talang Jarang Village, Air Napal District, North Bengkulu Regency, whose objects are farmers in Talang Jarang Village. In this community service activity, the researcher used the socialization method. The main focus of this activity is to introduce the community to Islamic finance, in order to help the community get capital. The community service program is carried out with the following stages: a. pre-training, b. education, c. evaluation. From the results of the study in the form of education for the farming community in Talang Jarang Village, it can be said that it has succeeded in providing an understanding of Islamic financial literacy education for farmers. It can be seen from the enthusiasm of the community in educational activities that get a very good response from the target audience by raising public awareness of the existence of Islamic finance, so that the community is interested in trying Islamic financial products.